Men's reproductive coercion of women: prevalence, experiences, and coping strategies-a mixed method study in urban health facilities in León, Nicaragua - Cecilia Brenner; William J. Ugarte; Ida Carlsson; Mariano Salazar (BMC, 2021)
Abstract Background Reproductive coercion (RC) is a common form of violence against women. It can take several expressions aiming at limiting women's reproductive autonomy. Thus, the frequency and how reproductive coercion can be resisted must be investigated. There is limited research regarding RC in Latin America. Therefore, this study aimed to measure RC prevalence and associated factors and to explore the women experiences and coping strategies for RC. Methods A convergent mixed-methods study with parallel sampling was conducted in Nicaragua. A quantitative phase was applied with 390 women 18-35 years old attending three main urban primary health care facilities. Lifetime and 12 months of exposure to RC behaviors including pregnancy promotion (PP) and contraceptive sabotage (CS) were assessed. Poisson regression with a robust variance estimator was used to obtain adjusted prevalence rate ratios and 95% Confidence Intervals (CIs). In addition, seven in-depth interviews were collected and analyzed using qualitative content analysis. Results Ever RC prevalence was 17.4% (95% CI, 13.8-21.6) with similar proportions reporting ever experiencing PP (12.6%, 95% CI 9.4-16.3) or ever experiencing CS (11.8%, 95% CI 8.7-15.4). The prevalence of last twelve months RC was slightly lower (12.3%, 95% CI, 9.2-16.0) than above. Twelve months PP (7.4%, 95% CI 5.0-10.5) and CS (8.7%, 95% CI 6.1-12.0) were also similar. Women's higher education was a protective factor against ever and 12 months of exposure to any RC behaviors by a current or former partner. Informants described a broad spectrum of coping strategies during and after exposure to RC. However, these rarely succeeded in preventing unintended pregnancies or regaining women's long-term fertility autonomy. Conclusions Our facility-based study showed that men's RC is a continuous phenomenon that can be enacted through explicit or subtle behaviors. Women in our study used different strategies to cope with RC but rarely succeeded in preventing unintended pregnancies or regaining their long-term fertility autonomy. Population-based studies are needed assess this phenomenon in a larger sample. The Nicaraguan health system should screen for RC and develop policies to protect women's reproductive autonomy.